Cannabis Use and Moral Judgment Among College Students - Chabrol, Henri; Bronchain, Jonathan; Raynal, Patrick; Gibbs, John (Journal of alcohol and drug education, 2019)
The aim of the present study was to evaluate the contribution of the maturity of moral judgment on cannabis use among college students. Participants were 1572 college students who completed self-report questionnaires measuring cannabis use, maturity of moral judgment, and emotional and personality variables. Thirty five percent of men and 30% of women reported having used cannabis at least once during the last 6 months. Logistic regression analysis found that the maturity of moral judgment was a significant predictor of cannabis use versus non-use. This study suggests the importance of evaluating moral judgment in studies of risk factors of cannabis use and to develop effective and non-moralizing interventions targeting permissive beliefs and other socio-cognitive variables determining cannabis use and misuse.